Does Ruxolitinib, in Comparison to Best Available Therapy (BAT), Improve Pruritis Symptoms in Patients with Polycythemia Vera?: A Systematic Review - Zachary Samuel Thorogood (Medical Research and Its Applications Vol. 9, 2024)
This systematic review evaluated three randomized controlled trials comparing the efficacy of the Janus kinase inhibitor ruxolitinib in the treatment of polycythemia vera and its reduction of pruritus symptoms in patients with symptomatic polycythemia vera. Polycythemia vera manifests as a myeloproliferative neoplasm associated with diverse symptoms, including aquagenic pruritis. Symptoms associated with polycythemia vera are related to blood hyperviscosity. Most patients can experience a broad range of symptoms including fatigue, pruritis, muscle aches, sweating, shortness of breath, erythromelalgia, and splenomegaly. The rarity and low prevalence of polycythemia vera underscore the importance of this investigation, as an existing standard of care involves a multifaceted approach and significant healthcare costs. Despite advancements in therapeutic options, persistent symptoms and resistance to first-line treatments pose challenges. Ruxolitinib has emerged as a promising intervention, demonstrating clinically significant improvement for patients. This systematic review appraises three randomized controlled trials, shedding light on the efficacy of ruxolitinib and its potential to ameliorate pruritis symptoms in symptomatic patients. Further studies focusing specifically on the longer-term evaluation of ruxolitinib compared to the best available therapy, as it pertains to symptomatic improvement, are warranted to determine whether there is a true statistical significance.